Prediction of biological activity of spiroquinazolone derivatives as protein kinase inhibitors FGFR1 and CK2 - O. K. Farat; S. A. Varenychenko; V. I. Markov (Zaporozhye State Medical University, 2020)
The purpose. The search for FGFR1 and CK2 protein kinase inhibitors were performed among spiroquinazolone derivatives using receptor-oriented virtual screening and in vitro biochemical testing using the human CK2 kinase domain. Materials and methods. The docking was performed at ATP binding sites for protein kinases CK2 and FGFR1 using the Autodock4 program. The inhibitory activity of the studied compounds against the protein kinase CK2 was determined by the inclusion of a phosphate group-containing radioactive 32P in the peptide substrate when it was phosphorylated by the kinase in the presence of γ-32P-ATP. Results. Testing results for the selected compounds showed that when added to an IC50 concentration of 10 µM, the protein kinase residual activity was more than 45 %. Conclusions. The results of the analysis of LogP and LogS indicated that the optimization of spiroquinazolone derivatives should be carried out in the direction of increasing the hydrophobicity of these compounds.